Improvement of algal-alginate bead stability by zeolite molecular sieves 13X and its application in biosorption - Moghaddam, Seyed Amirebrahim Emami (2019)
The interest in utilizing algae for wastewater treatment has been increased due to many advantages. Algae-Wastewater treatment system offers a cost-efficient and environmentally friendly alternative to conventional treatment processes. However, the recovery of free suspended algae from the treated effluent is one of the challenges during the treatment process. Therefore, the application of immobilized algae is a good approach to resolve the harvesting issue. Up to now, most of the algal immobilization has been done using cell entrapment method in which alginate (a natural polymer) has been applied as a carrier. Although alginate provides advantages in terms of biocompatibility, nontoxicity, cost-effectiveness, etc., this material has low stability to the chelating agents and a similar charge with cell surface of microorganisms, hence, it easily contributes to the leakage of large molecules due to the open lattice structure. Therefore, this study aims to improve the stability of Chlorella-Alginate Beads (CABs) by zeolite molecular sieves 13X (an aluminosilicate mineral with sodium ion) and further examined the potential use of the synthesized Zeolite 13X-Algal-Alginate Beads (ZABs) for copper biosorption from aqueous solution.